Design, synthesis and applications of responsive macrocycles - Jingjing Yu; Dawei Qi; Jianwei Li (NATURE RESEARCH, 2022)
Macrocycles have been widely studied for their structure-specific and highly selective recognition properties. Here the authors review the design, synthesis and applications of photo-, pH- and redox-responsive macrocycles.Inspired by the lock and key principle, the development of supramolecular macrocyclic chemistry has promoted the prosperous growth of host-guest chemistry. The updated induced-fit and conformation selection model spurred the emerging research on responsive macrocycles (RMs). This review introduces RMs, covering their design, synthesis and applications. It gives readers insight into the dynamic control of macrocyclic molecules and the exploration of materials with desired functions.